H1N1-associated Acute Necrotizing Encephalopathy of Childhood: Successful Treatment with the “Zipper Method” and Long-Term Outcome - Azapagasi, Ebru; Kesici, Selman; Kucur, Ozge; Gulenc, Nazli; Tasci Yildiz, Yasemin; Aksoy, Ayse (Iranian Journal of Child Neurology, 2025)
Acute necrotizing encephalopathy of childhood (ANEC) is a devastating childhood disease characterized by rapid neurologic deterioration after a viral febrile illness. Seizures, encephalopathy, and fatal acute necrotizing encephalopathy are well-defined neurologic complications of H1N1 virus infections. Symmetrical, multifocal lesions on cranial magnetic resonance imaging (MRI) are the best-known features of ANEC. Various treatment options include glucocorticoids, intravenous immunoglobulin (IVIG), and plasma exchange (PEX). Herein, we present a 45-month-old girl diagnosed with ANEC and treated with a novel immunomodulation technique, the “zipper method.” It is a combined treatment method in which PEX and IVIG treatments are used together. In the first session of plasma exchange, one and a half volumes of patients’ plasma were removed using 5% albumin as a replacement solution. At the end of the PEX session, 0.4 g/kg IVIG infusion was started. The second PEX session was applied with one volume 24 hours after the end of the IVIG infusion. This plasma exchange–intravenous immunoglobulin cycle was repeated five times. Furthermore, this case report presents her outcome 3-years after discharge: full recovery. This case is a unique example of ANEC treated successfully with the zipper method